2014
DOI: 10.1128/iai.02541-14
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica Fatty Acid Binding Protein Induces the Alternative Activation of Human Macrophages

Abstract: The liver fluke Fasciola hepatica is a highly evolved parasite that uses sophisticated mechanisms to evade the host immune response. The immunosuppressive capabilities of the parasite have been associated with antigens secreted through the parasite's tegument, called excretory-secretory products (ESPs). Proteomic studies have identified the fatty acid binding protein (FABP) as one of molecules present in the parasite ESPs. Although FABP has been investigated for potential use in the development of vaccines aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 52 publications
6
40
0
2
Order By: Relevance
“…After the purification process, fractions containing a polypeptide band of around 12kDa with isoelectric points of 5.1 to 7.25 were confirmed as FABP1 by mass spectrometry and its purity verified by 12.5% SDS-PAGE as recently reported (29). Fh12 gave endotoxin levels lower than 0.1 EU/ml, which is similar to background levels and to complete RPMI medium, so the purified Fh12 protein was considered to be endotoxin free.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…After the purification process, fractions containing a polypeptide band of around 12kDa with isoelectric points of 5.1 to 7.25 were confirmed as FABP1 by mass spectrometry and its purity verified by 12.5% SDS-PAGE as recently reported (29). Fh12 gave endotoxin levels lower than 0.1 EU/ml, which is similar to background levels and to complete RPMI medium, so the purified Fh12 protein was considered to be endotoxin free.…”
Section: Resultssupporting
confidence: 71%
“…We previously demonstrated that Fh12 exerts a strong immunomodulatory effect on human macrophage-derived monocytes (29). Our results here demonstrate that in the presence of Fh12 alone, bmMΦs do not express pro-inflammatory or inflammatory cytokines, which suggests that Fh12 does not activate any TLR on macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations